Analisis Penerapan Learning Management System Dalam Pengelolaan Pembelajaran - Ayuni, Sri; Kamila, Nada; Mabruroh, Amaliatul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study investigates the implementation of the Learning Management System (LMS) known as Apel Kansa Berduri at SD Negeri Kangenan 1 Pamekasan, focusing on its role as a digital innovation in primary education. The background of the study highlights the increasing necessity for effective and adaptive learning management in response to the rapid advancement of information and communication technologies. Using a descriptive qualitative approach, data were gathered through interviews, classroom observations, and document analysis. The results reveal that the LMS facilitates teachers in organizing, delivering, and assessing instructional content through interactive features such as digital textbooks, video materials, and online quizzes. Although teachers initially faced difficulties in adapting to the technology, these challenges were progressively overcome through systematic and continuous training. The integration of the LMS has contributed to improved instructional efficiency and enhanced student learning outcomes. Therefore, the adoption of Apel Kansa Berduri is considered a strategic step in transforming traditional classroom instruction into a modern, technology-integrated, and student-centered learning environment within Indonesia’s primary education system.